Determinants of Working Capital Investment in South Africa: Evidence from Selected JSE-Listed Firms - Kwenda, Farai (Journal of Economics and Behavioral Studies, 2014)
This paper analyses the determinants of working capital investments of 92 companies listed on the Johannesburg Stock Exchange (JSE) over the period 2001-2010. Working capital management has grown in significance from being a survival issue to a strategic and competitive tool. Using the Generalized Method of Moments estimation, the study found that firms pursue target levels of current assets. However, the adjustment process is relatively slow. The study found that leverage, short-term finance and fixed investment significantly influence the level of working capital investment, while operating cash flows, state of the economy, firm size and sales growth rate were found to be statistically insignificantly related to working capital investment. The study recommends that managers understand the driving factors of working capital investment since working capital investment influences the value of the firm.